THE CONSTRUCTION OF PROFESSIONAL CHOICE IN THE DECISION TO STUDY ARCHITECTURE (Editora Impacto Científico, 2025)
A common memory from childhood is the classic question: "What do you want to be when you grow up?" Behind this seemingly simple inquiry lies not only adult curiosity but also the beginning of a subjective process of identity formation and future projection. This article reflects on the vocational decision-making process, particularly during high school, through the lens of Howard Gardner's theory of multiple intelligences and Daniel Goleman's concept of emotional intelligence. Using a theoretical and interpretive approach, the text explores how specific cognitive and emotional competencies shape students' inclinations, with an emphasis on the choice of architecture as a career. The argument presented is that professional choices are not merely rational decisions but arise from a unique combination of abilities and sensitivities that intuitively guide the student toward what feels most familiar and meaningful.DOI: https://doi.org/10.56238/edimpacto2025.090-080